Perfeccionamiento de la técnica del estilo espalda a través del método lúdico en el club little fish de la ciudad de Riobamba durante el periodo 2022 - Ñauñay Chicaiza, Rosa Elena (2023)
The research centers on augmenting swimming instruction through the incorporation of recreational components to render learning appealing while simultaneously refining the backstroke technique. The principal aim of this investigation is to assess the efficacy of the ludic method in enhancing the mastery of the backstroke technique among juvenile swimmers. The study is conducted at the Little Fish Club in Riobamba, where participants are segregated into two distinct cohorts: one receiving conventional instruction and the other benefiting from the ludic approach. Employing a mixed methods approach, the research encompasses the acquisition of quantitative data via performance assessments. The gathered data is subjected to statistical analyses to discern the impact of the ludic approach on the enhancement of skills. The hypothesis posits that the ludic method engenders superior advancements in backstroke technique compared to conventional instruction. Substantiating this hypothesis, the study reveals that participants subjected to the ludic method manifest substantial enhancements in backstroke technique. The conclusions of the study emphasize the significance of infusing recreational elements into swimming instruction; the ludic method not only amplifies skill development but also ensures sustained engagement and enthusiasm among learners. The ensuing discussion delves into the broader implications of the findings within the context of swimming pedagogy, accentuating the potential of the ludic approach to reshape teaching methodologies, aligning with individualized learning proclivities and nurturing enduring interest in swimming. The proposal supports the continued integration of the playful method into the swim instruction curriculum, and suggests that instructors and program coordinators adopt this innovative approach